Developing Set of Word Senses of Vocabulary in Al-Qurâ€™an - Neca Aqila; Mochammad Arif Bijaksana (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Al-Qurâ€™an has become the guideline for all Muslims in the world, which makes many Muslims are eager to understand its contents. Nevertheless, Al-Qurâ€™an consist of many words that have more than one meaning, which represent certain difficulties while understanding the meaning itself. As example, the word Ø£ÙŽØ²Ù’ÙˆÙŽØ§Ø¬Ù‹Ø§ has two equivalents as it might be translated either "jodoh" (â€œmateâ€) in Surah An-Nahl (16: 72: 6) and "golongan-golongan" (â€œgroupsâ€) in Surah Al-Hijr (15: 88: 8). This case is known as a word sense, a word that has more than one meaning. This research aims to construct the word sense as a set of vocabulary, in order to simplify the vocabulary meaning in Al-Qurâ€™an itself. The data set used in this research is nouns from Al-Qurâ€™an which have been translated into Bahasa. In order to construct the set of word sense, this research grouped the words using Hierarchical Clustering method. The total set of the word senses found is 34 nouns, which contains diverse translation. The F measure from evaluation of this research resulted in an accuracy of 65.85%. The result was obtained based on the conformity between the results of the word senses set by the system and by the linguists. The outcome of this research is, accuracy is low, due to the type and the number data used is limited.